General Geology and Petrophysical Properties of Interval II (200 M to 300 M) in Well CTW01: Input for the Geologic Model of Seri Iskandar - Sulaiman, Mohamad Noor Solehin (2016)
A shale volume model for Seri Iskandar, Perak is presented in this study using lithofacies and petrophysical properties input based on well CTW01 and outcrops in Seri Iskandar area. This paper presents results of 200 meter to 300 meter interval for well CTW01.